Strong genetic differentiation due to multiple founder events during a recent range expansion of an introduced wall lizard population - Schulte, Ulrich; Veith, Michael; Mingo, Valentin; Modica, Corrado; Hochkirch, Axel (Biological invasions, 2013)
Biological invasions represent ideal systems for the study of evolutionary processes associated with colonization events. It has been hypothesized that the genetic diversity is generally decreasing from the centre of the range to the margins due to multiple founder events. Invasive populations offer the opportunity to test this hypothesis at a fine spatial and temporal scale. We analysed the genetic structure of a large expanding non-native population of the Common Wall Lizard ( Podarcis muralis ) in Passau (Germany) using thirteen microsatellite loci. We analyzed the genetic structure and levels of admixture across a transect reflecting the expansion process and tested for a loss of genetic diversity and an increase of genetic differentiation from the centre to the invasion front. Our results demonstrate that significant genetic population structure can emerge rapidly at a small spatial scale. We found a trend for an increase in genetic differentiation and a decrease in genetic diversity from the invasion centre to the expanding range margin, suggesting that genetic drift is the major factor causing this pattern. The correlation between genetic diversity and average genetic differentiation was significant among sites. We hypothesize that the territoriality of P. muralis generates sufficient rates of noncontiguous and stratified dispersal from longer established sites to maintain significant genetic diversity at the invasion front. Simultaneously, territoriality might restrict the colonization success of migrants at established sites, so that in combination with founder events a strong differentiation arises.